Interrelations between reading aloud and reading comprehension from the teachers’ perspective - Густі Ілона; Huszti Ilona (My University, 2017)
Abstract. The article describes the relationships between reading aloud in English and reading comprehension. The author intends to analyse them from the perspective of teachers of English as a foreign language.

Резюме. У статті розглядаються взаємозв’язки між читанням вголос та розумінням прочитаного тексту англійською мовою. Автор має намір їх проаналізувати з перспективи викладачів англійської як іноземної мови.
https://d6scj24zvfbbo.cloudfront.net/12ac69b5c0bec343f11779551473023e/200000195-31e1132dae/%D0%97%D0%B1i%D1%80%D0%BD%D0%B8%D0%BA%2031.pdf?ph=0a30397da1
Keywords: reading aloud; reading comprehension; teachers of English as a foreign language; читання вголос; розуміння прочитаного тексту; викладачі англійської як іноземної мови